2022
DOI: 10.1002/ajhb.23731
|View full text |Cite
|
Sign up to set email alerts
|

Is age of menarche directly related to vitamin D levels?

Abstract: Introduction Very few studies have examined the direct link between age of menarche and vitamin D level and controversial results have been reported. This study aimed to investigate the association between vitamin D and age of menarche in a group of adolescent girls in an area with plenty of sunshine. Methods At baseline, data were collected on 722 middle schoolgirls that were randomly selected by probability proportional to size sampling method. Of this group, 598 were followed including 173 who had their men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Al-Taiar et al [77] reported the association between 25OHD levels and age of menarche in Kuwait with a cross-sectional study and a prospective cohort study on 722 middleschool girls while also adjusting for potential confounders such as BMI, waist-height ratio, physical activity, and socioeconomic factors [77]. Even in this study, in which just the "severe deficiency category" was considered, no significant correlations between age of menarche and 25OHD status were observed [77]. The different results reported in the above-mentioned studies, performed in very different ethnic groups, might be secondary to the variability in human VDR gene polymorphisms that has been observed in different populations [78].…”
Section: Vitamin D Levels and Age Of Menarchementioning
confidence: 99%
See 2 more Smart Citations
“…Al-Taiar et al [77] reported the association between 25OHD levels and age of menarche in Kuwait with a cross-sectional study and a prospective cohort study on 722 middleschool girls while also adjusting for potential confounders such as BMI, waist-height ratio, physical activity, and socioeconomic factors [77]. Even in this study, in which just the "severe deficiency category" was considered, no significant correlations between age of menarche and 25OHD status were observed [77]. The different results reported in the above-mentioned studies, performed in very different ethnic groups, might be secondary to the variability in human VDR gene polymorphisms that has been observed in different populations [78].…”
Section: Vitamin D Levels and Age Of Menarchementioning
confidence: 99%
“…Only a few studies in the literature itself have examined the association between vitamin D status and age of menarche [71,76,77].…”
Section: Vitamin D Levels and Age Of Menarchementioning
confidence: 99%
See 1 more Smart Citation